UV-mediated hydrophosphinylation of unactivated alkenes with phosphinates under batch and flow conditions. Issue 15 (23rd February 2018) - Gelat, Fabien; Roger, Maxime; Penverne, Christophe; Mazzad, Ahmed; Rolando, Christian; Chausset-Boissarie, Laëtitia
Abstract : In this study, we report an efficient UV-mediated hydrophosphinylation of unactivated alkenes with H -phosphinates and hypophosphorous acid under radical free conditions in batch and in continuous flow. Abstract : A UV-mediated hydrophosphinylation of unactivated alkenes with H -phosphinates and hypophosphorous acid under radical free conditions is presented. The reaction affords selectively a large number of structurally diverse organophosphorous compounds in moderate to good yields under mild reaction conditions in the presence of an organic sensitizer as catalyst irradiated by UV-A LEDs. Furthermore, the high yielding hydrophosphinylation in continuous flow is disclosed.